Regulation of Fc Receptor Endocytic Trafficking by Ubiquitination - Molfetta, Rosa; Quatrini, Linda; Gasparrini, Francesca; Zitti, Beatrice; Santoni, Angela; Paolini, Rossella (Frontiers in Immunology, 2014)
Most immune cells, particularly phagocytes, express various receptors for the Fc-portion of the different immunoglobulin isotypes (Fc receptors, FcRs). By binding to the antibody, they provide a link between the adaptive immune system and the powerful effector functions triggered by innate immune cells such as mast cells, neutrophils, macrophages, and NK cells. Upon ligation of the immune complexes, the downstream signalling pathways initiated by the different receptors are quite similar for different FcR classes leading to the secretion of preformed and de novo synthesized pro-inflammatory mediators. FcR engagement also promotes negative signals through the combined action of several molecules that limit the extent and duration of positive signalling. To this regard, ligand-induced ubiquitination of Fc receptors for IgE (FcεR) and IgG (FcγR) has become recognized as a key modification that generates signals for the internalization and/or delivery of engaged receptor complexes to lysosomes or cytoplasmic proteasomes for degradation, providing negative-feedback regulation of Fc receptor activity. In this review, we discuss recent advances in our understanding of the molecular mechanisms that ensure the clearance of engaged Fcε and Fcγ receptor complexes from the cell surface with an emphasis given to the cooperation between the ubiquitin pathway and endosomal adaptors including the endosomal sorting complex required for transport (ESCRT) in controlling receptor internalization and sorting along the endocytic compartments.